Sensitivity of global and regional poverty rates to alternative purchasing power parities. Issue 1 (9th April 2018) - Majumder, Amita; Ray, Ranjan; Santra, Sattwik
Abstract : Purpose: The purpose of this study is to examine the sensitivity of regional and world poverty rates to the purchasing power parities (PPP) used in the calculations. The PPPs are required to convert the "international poverty line" typically denominated in US dollar to its local currency equivalent in the various countries. While recent studies on world poverty differ with respect to the specification of the international poverty line (IPL), they universally use the PPP available from the international comparison program (ICP). This study provides a departure and calculates PPPs using the Gini–Elteto–Koves–Szulc (GEKS) price index and country product dummy (CPD) model as alternatives to the ICP PPPs. The GEKS and CPD PPPs are compared with the ICP PPPs. The paper then compares the global and regional poverty rates based on the three sets of PPPs and presents evidence of significant revision to the poverty rates if we depart from the use of the ICP PPPs. The study tests for the presence of serial correlation between price movements in different countries and investigates its impact on the PPPs. The methodological contribution of this paper is to establish the close nexus between price indices and poverty rates via the PPPs used in obtaining the local currency unit (LCU) denominated IPL. Design/methodology/approach: The PPP calculations in this paper relate to the ICP round, 2011. Along with the ICP PPPs from published reports (with India as the numeraire country), we report the following indices, namely, the GEKS, weighted CPD and its two spatially correlated generalisations. The ICP PPPs are used as benchmark. The ICP group in the World Bank made the price and expenditure information for 2011 available. Corresponding poverty rates are calculated at the country, regional and global levels. Findings: The empirical evidence points to the fact that while at the country level the alternative calculations have high impact on the implied poverty rates, at the regional and global level the rates are reasonably quite robust. Research limitations/implications: Three points are worth noting, namely, as opposed to the PPP for "Individual consumption expenditure by households" (ICEH), which is the PPP used for international poverty monitoring by the World Bank and others, we have used the ICP PPPs for "Actual individual consumption" (AIC); although ICP uses the GEKS procedure above the BH level, we independently calculated these PPPs using the price information provided, and the base country has been moved from the USA to India. Practical implications: One can come up with independently estimated PPPs that do not require the elaborate and expensive procedure set up by the ICP and can arrive at robust poverty rates at the regional and global level. Social implications: The change in base has been made as India shares many of the features of a developing country including high poverty rates, but at the same time provides a market and an economy size that places it in the top tier of nations. In addition, poverty comparisons amongst developing countries can be made using these PPPs directly, without reference to the USA. The poverty calculations are based on the PovcalNet program. Originality/value: There is no clear answer to the question "how robust are the global poverty numbers to departures from the ICP PPPs?" in the literature nor is there any evidence on the robustness of the ICP PPPs themselves to changes in the ICP methodology. Given that the ICP uses the Gini–Elteto–Koves–Szulc (GEKS) multilateral price index in aggregation of ICP PPP basic heading data, in an attempt to partially answer this question this study examines the sensitivity of measures of relative prices (and poverty) to using CPD (and various spatial versions) and GEKS methods, using price data provided by the World Bank. It also verifies how these PPPs track the published 2011 ICP PPPs, which are used as benchmark.